Skeletal muscle and performance adaptations to high-intensity training in elite male soccer players: speed endurance runs versus small-sided game training - Fransson, Dan; Nielsen, Tobias Schmidt; Olsson, Karl; Christensson, Tobias; Bradley, Paul S.; Fatouros, Ioannis G.; Krustrup, Peter; Nordsborg, Nikolai Baastrup; Mohr, Magni (European journal of applied physiology, 2018)
Purpose To examine the skeletal muscle and performance responses across two different exercise training modalities which are highly applied in soccer training. Methods Using an RCT design, 39 well-trained male soccer players were randomized into either a speed endurance training (SET; n = 21) or a small-sided game group (SSG; n = 18). Over 4 weeks, thrice weekly, SET performed 6–10 × 30-s all-out runs with 3-min recovery, while SSG completed 2 × 7–9-min small-sided games with 2-min recovery. Muscle biopsies were obtained from m. vastus lateralis pre and post intervention and were subsequently analysed for metabolic enzyme activity and muscle protein expression. Moreover, the Yo–Yo Intermittent Recovery level 2 test (Yo–Yo IR2) was performed. Results Muscle CS maximal activity increased ( P < 0.05) by 18% in SET only, demonstrating larger ( P < 0.05) improvement than SSG, while HAD activity increased ( P < 0.05) by 24% in both groups. Na + –K + ATPase α 1 subunit protein expression increased ( P < 0.05) in SET and SSG (19 and 37%, respectively), while MCT4 protein expression rose ( P < 0.05) by 30 and 61% in SET and SSG, respectively. SOD2 protein expression increased ( P < 0.05) by 28 and 37% in SET and SSG, respectively, while GLUT-4 protein expression increased ( P < 0.05) by 40% in SSG only. Finally, SET displayed 39% greater improvement ( P < 0.05) in Yo–Yo IR2 performance than SSG. Conclusion Speed endurance training improved muscle oxidative capacity and exercise performance more pronouncedly than small-sided game training, but comparable responses were in muscle ion transporters and antioxidative capacity in well-trained male soccer players.